MURTAD: ANTARA HUKUMAN MATI DAN KEBEBASAN BERAGAMA (Kajian Hadis dengan Pendekatan Tematik) - Abd. Rahman Dahlan (State Islamic University North Sumatra, 2008)
Abstract: Apostasy: Between Death Penalty and Religious Freedom: A Thematic Study of Hadîth. One of the most sensitive discussions in Islamiclaw is the issue of apostasy. Some scholars of Islam maintain that the dead penalty for the apostate found in the precept of Islamic law is perceived as contrary to human rights, since it is against the principles of religious freedom. This paper presents a different perspective, which explains that this allegation is not entirely true. Not merely because of the apostasy. By using thematic hadis approach, this essay attempt to proof that it is apostasy which combined with rivalry against the state and enmity against Islam (bughât) that can be penalized with death sentence. And this can be executed after the state have decided to do so. Kata Kunci: murtad, kebebasan beragama, doktrin, qânûn